2004
DOI: 10.1007/s00464-003-9263-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life after laparoscopic surgery: evidence-based guidelines of the European Association for Endoscopic Surgery

Abstract: Background: Measuring health-related quality of life (QoL) after surgery is essential for decision making by patients, surgeons, and payers. The aim of this consensus conference was twofold. First, it was to determine for which diseases endoscopic surgery results in better postoperative QoL than open surgery. Second, it was to recommend QoL instruments for clinical research. Methods: An expert panel selected 12 conditions in which QoL and endoscopic surgery are important. For each condition, studies comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
153
0
16

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(174 citation statements)
references
References 129 publications
3
153
0
16
Order By: Relevance
“…[39][40][41][42][43] Our subjects' results were consistent with these findings. The SF-36 s has been recommended at a consensus conference of bariatric surgeons 44 and the SF-12 s has demonstrated internal validity in a bariatric population. 45 Obese subjects are more likely to somatize and to be depressed than normal-weight controls, 46,47 which can impact on pain and pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43] Our subjects' results were consistent with these findings. The SF-36 s has been recommended at a consensus conference of bariatric surgeons 44 and the SF-12 s has demonstrated internal validity in a bariatric population. 45 Obese subjects are more likely to somatize and to be depressed than normal-weight controls, 46,47 which can impact on pain and pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…Following a SR of the evidence one clinical practice guideline (CPG) showed that LC improves quality of life sooner than open cholecystectomy. Nevertheless, long-term LC results were similar to the open procedure (Korolija, 2004), (Treatment studies 1a); and a prospective cohort supports the utility of LC by showing not only a significant reduction of GI postoperative symptoms but also marked improvement in patients' general QOL (Finan, 2006).…”
Section: (Treatment Studies 1a)mentioning
confidence: 52%
“…(High quality evidence). LC seems a relatively safe procedure for special groups of patients such as the elderly, pregnant women or patients with cirrhosis and portal hypertension Child A y B (Low quality evidence) (ANDEM, 1994;Downs, 1996;Korolija, 2004;Mimica, 2000;Ros, Clinical High quality: it is very unlikely that future studies change our confidence in the estimate of effect and therefore our confidence is high. Moderate quality: it is likely that future studies change our confidence in the estimate of effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being an invasive procedure involving general anaesthetic, SL offers these patients tremendous benefit (early commencement of alternative treatment strategies [38], shortened hospital stay, psychological benefit of minimally invasive surgery [39]) with very little risk (failure rate ~ 1%, morbidity, mainly minor < 0.5%, and mortality < 0.05%).…”
Section: Discussionmentioning
confidence: 99%